Size-controlled preparation of ruthenium nanoparticles using polyaromatic amine-containing compounds as hydrogenation nanocatalyst precursors - Eblagon, K; Valdes-Solis, T; Kerry Yu, K; Ramirez-Cuesta, A; Tsang, S (2010)
Ruthenium nanoparticles stabilised by polyaromatic amine-containing compounds (aminoethylcarbazole, aminoanthracene and aminoanthraquinone) were synthesised in solution using three different preparative methods, namely modified polyol reduction, borohydride reduction and phase-transfer method, respectively. Their product yields, particle sizes and size distributions were compared accordingly. The influence of stirring speed, amount of protecting agent, reduction temperature and ageing time were widely investigated. The phase transfer between polar and non-polar phases using these new polyaromatic stabilisers was optimised but found to be less efficient than those particles stabilised with alkylamine, due to the weaker mode of amine adsorption on the metal surface. The interactions of stabilisers with the metal surface were also analysed using infrared spectroscopy (IR), thermo gravimetric analysis (TGA) and energy dispersive x-ray analysis (EDX). These stabilised ruthenium nanocrystals were then preliminary studied as nanocatalysts for hydrogenation of cinnamylaldehyde which was employed as a reaction probe. Ruthenium nanoparticles prepared via modified polyol and borohydride reductions were both found to be highly active towards cinnamylaldehyde hydrogenation to hydro-cinnamylaldehyde in ethanol. © 2010 Inderscience Enterprises Ltd.